Kebijakan Formulasi Pengaturan “Illicit Enrichment” Sebagai Upaya Pemberantasan Tindak Pidana Korupsi - Milda Istiqomah (Jurnal Media Hukum, 2016)
In its progress, the criminal sanctions given to the convicted offenders of corruption are not effective. Therefore, in order to prevent corruption, the strategy needs a certain mechanism to criminalize the alleged offenders of corruption. The proper strategy is to provide a deterrent effect aims to impoverish corruptor. This study attempts to examine the regulations of corruption and offers alternative setting formulations of illicit enrichment as an effort to prevent the corruption. This research applies normative judicial method with statute approach and comparative approach. This study concludes that Indonesia doesn’t have regulations related to illicit enrichment; therefore the author offers an alternative on regulation of illicit enrichment as effort to eradicate corruption in Indonesia.